Conference on Lasers and Electro-Optics 2020
DOI: 10.1364/cleo_si.2020.sm1q.1
|View full text |Cite
|
Sign up to set email alerts
|

Tunable infrared light emission from MoS2/WSe2 heterostructures

Abstract: We report light emission around 1200 nm from a vertical heterostructure consisting of M0S2 and WSe2 monolayers. The emission, arising from the fundamental interlayer exciton, can be tuned by nearly 100 nm by electrical gating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 8 publications
5
67
0
Order By: Relevance
“…The enhanced lifetime for the misaligned sample could be an indication for the absence of the radiative decay channel as it was reported recently. 25 The difference in lifetime between quasi-2H and quasi-3R can then be explained by the same reasoning as the enhanced transfer. Since the charge transfer via a phonon-assisted tunneling process can be amplified by the spatial overlap of the involved wave functions, 6,28 the same should hold for the reversed process of interlayer exciton recombination: A stronger spatial coincidence facilitates the recombination resulting then in a reduced lifetime.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The enhanced lifetime for the misaligned sample could be an indication for the absence of the radiative decay channel as it was reported recently. 25 The difference in lifetime between quasi-2H and quasi-3R can then be explained by the same reasoning as the enhanced transfer. Since the charge transfer via a phonon-assisted tunneling process can be amplified by the spatial overlap of the involved wave functions, 6,28 the same should hold for the reversed process of interlayer exciton recombination: A stronger spatial coincidence facilitates the recombination resulting then in a reduced lifetime.…”
Section: Resultsmentioning
confidence: 93%
“…17 Recently, also momentum-space direct K−K photolumines-cence at ≈1.0 eV has been observed for well-aligned MoS 2 / WSe 2 heterostructures. 25 In the present study, we want to elucidate the corresponding ultrafast dynamics in dependence of the stacking angle for three selected stacking angles: 9°( referred to as quasi-3R), 52°(quasi-2H), and 16°( misaligned).…”
mentioning
confidence: 99%
“…Van der Waals stacking of those monolayer TMDs can provide a valid platform to explore rich physical processes including charge transfer, 9 many-body interactions, 10 coupled spin and valley physics, 11 and moirésuperlattices. 12 In particular, interlayer excitons (IXs) can be formed in the van der Waals stacked TMD heterobilayers 13,14 and carry the valley information. 15,16 Compared to the picosecond time scale of exciton valley depolarization in monolayer TMDs arising from the strong Coulomb interactions, 17 previous studies have revealed the nanosecond time scale of IXs in MoSe 2 /WSe 2 15,18 and MoS 2 / MoSe 2 19 and even extending to the microsecond time scale by applying an external magnetic field, 20 thus beneficial to the IXbased valleytronic devices 21 and low-threshold lasing.…”
mentioning
confidence: 99%
“…[6] Karni et al reproduced this direct interlayer exciton transition between the K valleys. [81] Their the oretical model from ab initio calculations suggested that the Γ point states hybridization rendered the Γ-K transition to be a mixed one (with inter and intralayer), giving rise to interlayer excitons with a weakened dipole moment.…”
Section: Tunable Wavelength From Near-ir To Mid-irmentioning
confidence: 99%